EULOGISING GOD IN CHRISTIAN WORSHIP THROUGH AKAN TRADITIONAL APPELLATIONS: A CASE OF KUMASI - Ansong, K. D.; Asante, Eric Appau; Kquofi, Steve (Advances in Social Sciences Research Journal, 2014)
Although Christianity has existed within the Kumasi Metropolis for over 100 years, Church worship has not been fully influenced by the rich indigenous cultural elements of the Akan. This is a result of the failure of the early white missionaries to fully appreciate and adapt Akan cultural elements like appellations in the liturgy of the Church. This paper therefore sought to look at the worship life of Christians of Kumasi with the view to discuss how some appellations in the Akan culture could be carefully integrated into Christianity in Kumasi. Since the study primarily focused on the description of the appellations in the ritual celebrations of Christian worship, the research problem was answered by adopting the qualitative research approach. Analysis was made to justify that Akan eulogy could also be adapted and used in Christian worship.